Karakteristik organoleptik pada produk olahan stik biji nangka - Ningrum Dwi Hastuti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Jackfruit seeds have high nutritional content such as carbohydrates, and protein, so they can be used as potential food. Processing jackfruit seeds into food products is one form of business utilizing jackfruit seed waste as an alternative to adding new food sources. The purpose of this study was to determine the organoleptic characteristics of jackfruit seed stick products. Organoleptic test using Friedman Test with α = 0.05 and determining the best treatment using the effectiveness index. The results showed that the best organoleptic test was obtained from jackfruit seed stick products with a product value of 0.610 with a mean value of the panelists' preference for taste of 4.40; color of 3.92 and flavour of 2.48